A theory of firm decline - Gian Luca Clementi; Thomas F. Cooley; Sonia Di Giannatale (Fondazione Eni Enrico Mattei (FEEM), 2010)
We study the problem of an investor that buys an equity stake in an entrepreneurial venture, under the assumption that the former cannot monitor the latter's operations. The dynamics implied by the optimal incentive scheme is rich and quite different from that induced by other models of repeated moral hazard. In particular, our framework generates a rationale for firm decline. As young firms accumulate capital, the claims of both investor (outside equity) and entrepreneur (inside equity) increase. At some juncture, however, even as the latter keeps on growing, invested capital and firm value start declining and so does the value of outside equity. The reason is that incentive provision is costlier the wealthier the entrepreneur (the greater is inside equity). In turn, this leads to a decline in the constrained-efficient level of effort and therefore to a drop in the return to investment.
Keywords: D82; D86; D92; G32; 330; Principal Agent; Moral Hazard; Hidden Action; Incentives; Survival; Firm Dynamics